2017
DOI: 10.1021/acs.jmedchem.7b00900
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Piperidine-Based Inhibitor of Cholesteryl Ester Transfer Protein (CETP) That Retains Activity in Hypertriglyceridemic Plasma

Abstract: Herein we describe the discovery and characterization of a novel, piperidine-based inhibitor of cholesteryl ester transfer protein (CETP) with a core structure distinct from other reported CETP inhibitors. A versatile synthesis starting from 4-methoxypyridine enabled an efficient exploration of the SAR, giving a lead molecule with potent CETP inhibition in human plasma. The subsequent optimization focused on improvement of pharmacokinetics and mitigation of off-target liabilities, such as CYP inhibition, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It may also be that anacetrapib reduces plasma levels of the proprotein convertase subtilisin kexin type 9 (PCSK9), which is one of the major regulators of LDLR. 97 Although the REVEAL trial has shown that anacetrapib could reduce the risk of major coronary events, as it is highly lipophilic and accumulated in adipose tissue during continued dosing 98 ; further regulatory approval is not be sought. Despite the development of effective HDL-raising drugs, large-scale clinical trials showed disappointing results with no significant reduction of clinical CV events.…”
Section: Cholesteryl Ester Transfer Protein (Cetp) Inhibitorsmentioning
confidence: 99%
“…It may also be that anacetrapib reduces plasma levels of the proprotein convertase subtilisin kexin type 9 (PCSK9), which is one of the major regulators of LDLR. 97 Although the REVEAL trial has shown that anacetrapib could reduce the risk of major coronary events, as it is highly lipophilic and accumulated in adipose tissue during continued dosing 98 ; further regulatory approval is not be sought. Despite the development of effective HDL-raising drugs, large-scale clinical trials showed disappointing results with no significant reduction of clinical CV events.…”
Section: Cholesteryl Ester Transfer Protein (Cetp) Inhibitorsmentioning
confidence: 99%
“…As a comparison to the previous data set, ca. 15 additional papers were surveyed from the Journal of Medicinal Chemistry ( JMC ) for both SMCC reactions ,, and Buchwald–Hartwig amination reactions. , As the previous data were found from a variety of journals, although largely catalysis specific, we were interested to see how different these would be compared to papers only reported in JMC and if there was a difference in mol % and ppm catalyst levels. Finding more papers with a greater focus on catalyst usage, rather than catalyst optimization, reveals a different angle to this study.…”
Section: Further Analysis Of Selected Articles Reported In the Journa...mentioning
confidence: 99%
“…Pyridine is frequently used in the chemical industry, primarily in the production of pesticides, as solvent, in the production of dyes, explosives, pharmaceuticals, and as ligand in specialty coordination chemistry synthesis (Ahsan et al, 2018;Liu et al, 1998;Shen et al, 2015). 4METPYR has been reported as ligand in coordination chemistry (Mautner et al, 2018) and as precursor for the synthesis of active principles by the pharmaceutical industry (Yamada et al, 2017). 3HYPYR has been investigated as a monomer for production of polymers for CO2 capture (Gutiérrez et al, 2011), but its primary use is as precursor for pharmaceutical active principles (Kaviani and Izadyar, 2018).…”
Section: Pyridinesmentioning
confidence: 99%